Improved Powder Equivalence Model for the Mix Design of Self-Compacting Concrete with Fly Ash and Limestone Powder - Jingbin Zhang; Miao Lv; Xuehui An; Dejian Shen; Xinyi He; Ding Nie (Advances in Materials Science and Engineering)
The use of fly ash (FA) limestone and powder (LP) in combination with cement in concrete has several practical, ecological, and economic advantages by reducing carbon dioxide emissions, reducing the excessive consumption of natural resources, and contributing to a cleaner production of self-compacting concrete (SCC). A mix design method for SCC based on paste rheological threshold theory can guide the SCC mix design by paste tests. This method can be visualized by the self-compacting paste zone (SCP zone), a plane area where all the mix points meet the paste threshold theory, and SCC zone, a plane area consisting of all the mix points satisfying the criteria of qualified SCC. In the case of cement SCC, the SCP zone coheres with the SCC zone. However, in the case of the addition of FA or LP with different granulometry and shape characteristics from cement, experimental results indicate that the SCP zone is separated from the SCC zone. This work quantitatively studied the influence of FA and LP on the movement of the SCP zone by introducing the improved powder equivalence model. The improved model was obtained by powder equivalence coefficients calculated through the mortar test results with or without FA or LP, instead of SCC tests in the former method. The equivalence coefficients by volume of FA and LP are 0.55 and 0.79, respectively, which means that 1.82 unit volume of FA or 1.27 unit volume of LP is equivalent to one unit volume of cement. The improved powder equivalence model was verified by the successful preparation of SCC incorporating FA or LP simply and effectively. The equivalent SCP zone cohered better with the SCC zone than the former SCP zone, which could guide the quick mix design of SCC without SCC premix tests.